Factors affecting the willingness to adopt Central Bank Digital Currency (CBDC) among undergraduate students in UTAR. - Chee, Shang Yi; Kong, Kah Kit; Ng, Zhe Khai (2024)
Due to the rapid economic and technological development, digital currency is gradually integrated into daily routine as a medium of exchange instead of physical cash. However, most digital currencies are decentralized but not managed by a centralized authority, leading to difficulty in controlling. A new type of digital currency known as CBDC which is fully controlled by a country’s central bank can tackle this issue. Hence, studies on willingness to adopt CBDC are being conducted by researchers. However, limited research on the opinion of undergraduate students is done. Hence, this study examines factors affecting willingness to adopt CBDC among undergraduate students in UTAR. The five independent variables examined are privacy factors, financial knowledge, openness to innovation, regulatory factors, and security factors. We collected responses from 393 undergraduate students in UTAR Kampar using surveys. Reliability test, multicollinearity test, and normality test are done before analyzing the relationship. Then, multiple linear regression analysis is used as inferential analysis to examine the relationship. All the tests run through SPSS 26.0. Our findings are all five independent variables have a significant and positive relationship with willingness to adopt CBDC. Therefore, government and agencies related should emphasize these factors when considering adopting CBDC.